Effects of Greenwashing on the Markets of the Western World - Mysirli, Thessalia; Axarli, Dimitra (HAPSc Policy Briefs Series, 2021)
With the beginning of the new century, more and more consumers from the western world have taken a step further towards sustainable decisions. This leads them to be conscious of the company they support and buy from. In order to keep up with consumers’ expectations, some companies have decided to promote a positive image of environmental performance, yet their real environmental performance has not changed. This practice is called greenwashing. This paper aims to take a closer look at this issue by using some case studies, and to inform the reader for some of the effects the act of greenwashing has brought into the surface in the western world.